Study of electrochromic materials using physical vapor deposition - Toh, Jia Sheng (2016)
Electrochromic thin films (Molybdenum oxide and Nickel Oxide) have been deposited using physical vapor deposition technique at room temperature. The first phase of this project focuses on the deposition of these electrochromic thin films on ITO glass and borosilicate glass. During optimization of these films, several parameters are varied such as oxygen flow rate, argon flow rate, oxygen partial pressure, deposition duration and duration for exposure of argon and oxygen prior to sputtering. The second phase of this project focuses on the characterization of these electrochromic films. The optical property, surface morphology and electrochromic property were investigated using spectrophotometry, atomic force microscopy and cyclic voltammetry.